Ecclesial and world view characteristics of Catholic charismatic renewal groups in the United Kingdom - Chappell, K (2017)
The Catholic Charismatic Renewal is one of the largest movements within the global Catholic Church and has been a significant part of Catholicism in the United Kingdom for nearly fifty years. In terms of theology, ethos and social structure it is poorly understood with little academic or critical analysis of the movement. This study seeks to address this through ethnographic research and theological analysis of the beliefs, behaviour and worldview of several expressions of the Catholic Charismatic Renewal in Britain and Northern Ireland. In doing so there is also an aim to evaluate the efficacy and value of three analytical approaches used by previous studies of religious groups and to consider their applicability in a broader context. The research reveals a diverse movement that is expressed through a broad range of groups and devotions, from covenant communities to small parish groups. Some key themes in ethos and theology were evident in all expressions of the movement, most important amongst these being eschatology. The role of cognitive dissonance in the development of this eschatology is considered as is the integration of the Charismatic movement into the host Catholic Church. A central role for Marian devotion in this process of catholicisation is identified and associated with the diversity of current expressions which represent differing stages in this process. The methodological approaches used are critically evaluated and, whilst value is identified in each one, the greatest potential for deep understanding and broader comparative studies is seen in the narrative approach put forward by James Hopewell. This approach is seen as allowing depth of understanding and a more nuanced consideration of apparently opposing beliefs or phenomena. Additionally, such a narrative approach is seen as having applicability beyond limited social and theological contexts.